Profil Hematologi Pasien Hipertiroid yang Mendapatkan Terapi Obat Antitiroid di Poliklinik Endokrin, Metabolik, dan Diabetes RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar Tahun 2023 - Made Aryadi Sukartika; Made Ratna Saraswati (MEDICINUS, 2026)
Introduction: Antithyroid drugs are one of the treatment options for hyperthyroidism, alongside surgery and radioactive iodine treatment. The antithyroid medications used are thiocarbamide/thiocyanate derivatives, such as propylthiouracil (PTU) and methimazole. Information on the characteristics of hyperthyroid patients, especially regarding possible hematological adverse effects such as agranulocytosis, thrombocytopenia, and pancytopenia, can assist physicians in considering treatment options. Methods: This descriptive, retrospective study used medical records to describe the hematological profile of hyperthyroid patients receiving antithyroid medication therapy at the Endocrine, Metabolic, and Diabetes Polyclinic of RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, Bali in 2023. Results: A total of 261 patients were included. The most common age range was 51–60 years (64 patients, 24.5%), and the majority were female (78.5%). The duration since hyperthyroidism diagnosis was most often <12 months (129 patients, 49.4%). The most frequent diagnosis was suspected Graves’ disease (187 patients, 71.6%), and most patients (210, 80.5%) had no comorbidity. In the methimazole group (218 patients, 83.5%), no patient (0%) developed agranulocytosis, 70 (32.1%) had hemoglobin <12 g/dl, and 14 (6.4%) had platelets <150 ×10³/μl. In the propylthiouracil group (43 patients, 16.5%), 1 patient (2.3%) developed agranulocytosis, 18 (41.9%) had hemoglobin <12 g/dl, and 3 (7%) had platelets <150 ×10³/μl. Discussion: The low occurrence of agranulocytosis (0% with methimazole and 2.3% with propylthiouracil) indicates that antithyroid drug-induced hematologic abnormalities are very rare, consistent with the reported figure of 0.2–0.5% in patients with Graves’ disease. Differences between groups may be influenced by study population characteristics, genetic factors, duration of drug use, and the unequal proportion of the two treatment groups. Conclusions: Hematologic abnormalities among hyperthyroid patients receiving antithyroid drugs were low and tended to be more frequent in the propylthiouracil group. Normal neutrophil counts were found in 191 patients (87.6%) of the methimazole group and 39 patients (90.7%) of the propylthiouracil group.